Experimental Study of the Influence of the Adsorbate Layer Composition on the Wetting of Different Substrates with Water. (12th January 2021) - Heier, Michaela; Merz, Rolf; Becker, Stefan; Langenbach, Kai; Kopnarski, Michael; Hasse, Hans
Abstract : Wetting is strongly influenced by adsorbate layers, which are omnipresent on surfaces. The influence of the composition and thickness of adsorbate layers on the water contact angle of sessile drops on different substrates was systematically investigated in the present work. Measurements were carried out for gold-sputtered substrates. These new results are compared to results from a previous study, in which corresponding measurements were carried out for technical steel and titanium substrates. In all experiments, different pretreatments of the samples were used to obtain variations of the adsorbate layer. The samples were either exposed to an oil bath or not, and different cleaning agents were used. The analysis of the adsorbate layer was carried out with X-ray photoelectron spectroscopy (XPS). The results for the different substrates reveal that the water contact angle depends mainly on the composition of the adsorbate layer. The substrate has only an indirect influence, as it influences the composition of the adsorbate layer. The thickness of the adsorbate layers was between 1.4 and 14 nm and was large enough to prevent a direct influence of the substrate on the water contact angle. It is shown that using the information on the adsorbate layer composition from XPS and the results for the water contact angle obtained for the gold samples alone, the water contact angles on the steel and titanium samples can be predicted.